Atmospheric ethanol in London and the potential impacts of future fuel formulations. (19th April 2016) - Dunmore, Rachel E.; Whalley, Lisa K.; Sherwen, Tomás; Evans, Mathew J.; Heard, Dwayne E.; Hopkins, James R.; Lee, James D.; Lewis, Alastair C.; Lidster, Richard T.; Rickard, Andrew R.; Hamilton, Jacqueline F.
Abstract : There is growing global consumption of non-fossil fuels such as ethanol made from renewable biomass. Previous studies have shown that one of the main air quality disadvantages of using ethanol blended fuels is a significant increase in the production of acetaldehyde, an unregulated and toxic pollutant. Most studies on the impacts of ethanol blended gasoline have been carried out in the US and Brazil, with much less focus on the UK and Europe. We report time resolved measurements of ethanol in London during the winter and summer of 2012. In both seasons the mean mixing ratio of ethanol was around 5 ppb, with maximum values over 30 ppb, making ethanol currently the most abundant VOC in London air. We identify a road transport related source, with 'rush-hour' peaks observed. Ethanol is strongly correlated with other road transport-related emissions, such as small aromatics and light alkanes, and has no relationship to summer biogenic emissions. To determine the impact of road transport-related ethanol emission on secondary species ( i.e. acetaldehyde and ozone), we use both a chemically detailed box model (incorporating the Master Chemical Mechanism, MCM) and a global and nested regional scale chemical transport model (GEOS-Chem), on various processing time scales. Using the MCM model, only 16% of the modelled acetaldehyde was formed from ethanol oxidation. However, the model significantly underpredicts the total levels of acetaldehyde, indicating a missing primary emission source, that appears to be traffic-related. Further support for a primary emission source comes from the regional scale model simulations, where the observed concentrations of ethanol and acetaldehyde can only be reconciled with the inclusion of large primary emissions. Although only constrained by one set of observations, the regional modelling suggests a European ethanol source similar in magnitude to that of ethane (∼60 Gg per year) and greater than that of acetaldehyde (∼10 Gg per year). The increased concentrations of ethanol and acetaldehyde from primary emissions impacts both radical and NO x cycling over Europe, resulting in significant regional impacts on NO y speciation and O3 concentrations, with potential changes to human exposure to air pollutants.